تنمية الحواس لدى الطفل التوحدي من خلال برنامج تجريبي قائم على استراتجية الحواس المتعددة فاكت دراسة ميدانية بالمركز النفسي البيداغوجي للأطفال المعوقين ذهنيا بلعباس محمد بأفلو - بلقاسمي عثمان; خنفار سامرة (My University, 2023)
The study aimed to reveal the effectiveness of using the multisensory strategy (VAKT) to develop the senses of children with autism at the Psychological and Pedagogical Center "Bel Abbas Mohamed" in the city of Aflou. The experimental scale, the application of the sensory list scale of Dr. Ahmed Abdel-Fattah, a specialist in communication and autism at the Federation of Arab Doctors, in addition to interview and observation, and the application of the multi-senses strategy program for developing the senses of the autistic child, prepared by the student researcher, the owner of the study and under the supervision of the professor, and after applying the program, we calculated the differences between the pre-measurement and telemetry, and the results reached the following: -measurement and the post-measurement (the mean of the pre-measurement is not equal to the mean of the post-measurement) Keywords: autism, VAKT, multisensory strategy.